Small Bowel Review: Part I - ABR Thomson; J Hasan; M Keelan; G Wild (Canadian Journal of Gastroenterology)
In the past year there have been many advances in the area of small bowel physiology and pathology. In preparation for this review, over 500 papers were assessed, and some have been selected and reviewed, with a particular focus on presenting clinically useful information for the practising gastroenterologist.